Sustentabilidade da tecnologia bioflocos sobre diferentes densidades de alevinos de tilápia do Nilo - Tavares , Sidnei Gregório (2021)
Biofloc farming technology (BFT) is an alternative for high density production, which maintains water quality and a minimum renewal rate, thus contributing to the goals sustainable development, resulting in higher productivity with less impact on the environment. In this context, this study was divided into two stages, in which, Stage I: aimed at the review study on the economic, social and environmental sustainability of biofloc biotechnology in the cultivation of Nile tilapia Oreochromis niloticus. With a systematic review, it was used as methodology the details of the exclusion and inclusion criteria adopted for the selection of the sample and analysis of the content of the publications. Metaanalysis was used, opting for the mixed nature, of articles published in scientific journals from 2008 to 2021. In this sense, studies involving the biotechnology of bioflocs contemplated in this meta-analysis belong especially to the technical order, followed by the sustainability of the technology used and positive aspects regarding the economic scope. However, there is a deficit in addressing the social aspects involved with the application of this biotechnology. Step II: The objective was to evaluate the effect of different stocking densities on the water quality of the BFT system, zootechnical performance, intestinal, hepatic and muscular physiology of Nile tilapia fingerlings. The rearing density of fingerlings was evaluated: 375, 750, 1,125 and 1,500 fish/m³ in a BFT system. It was concluded that the stocking density of 375 fish/m³ provided the lowest levels of ammonia and nitrite in the aquatic environment and the stocking density of 1125 fish/m³ provided the best productive performance, maintaining the physiological processes of the fish, in addition, guaranteed tolerable water quality levels for BFT cultivation.